Libidinosa amor. Sobre algunes fonts llatines en Lo somni. - GROS LLADÓS, SÒNIA (Scripta)
This paper explores some references in books III and IV of Lo somni on the question about «l'amor de fembres» and the pernicious effects of immoderated lust, from the perspective of the Latin sources used in the Catalan text. The analysis of Metge's reuse of some sources allows to examine the formal resources of his writing, as well as to delve into the connections of Bernat Metge with classical and Italian texts. Lo somni shows a new literary perspective and a clear philogynist attitude imitating the re-readings that the great masters of Trecento, Petrarch and Boccaccio, had made of Latin classics such as Valerius Maximus.